Estimation of faecal excretion in alpacas (Vicugna pacos) in confinement conditions using titanium dioxide - Camargo H., Rosina (2019)
The aim of this study was to estimate the production of faeces in alpacas with the use of titanium dioxide (TiO2). A square 4x4 Latin design was used, with four animals, four treatments and four periods. Each period last for 14 days of evaluation and seven days of rest. The treatments were: T2.5 (1), 2.5 g of TiO2/animal/day; T1.25(2), 2.5 g of TiO2/animal/day divided into two doses (07:00, 16:00); T5(1), 5 g of TiO2/animal/day; T2.5(2), 5 g of TiO2/animal/day divided into two doses (07:00, 16:00). The percentages of the recovery of TiO2 were 90, 82, 78 and 52% for T2.5(1), T1.25(2), T5(1) and T2.5(2), respectively, being T2.5(2) different from the other treatments (p=0.00013). The parameters of the TiO2 excretion pattern were: intercept of the curve of TiO2 excretion at time zero (a), maximum excretion of TiO2 at time (b), constant rate of excretion of b (c), time needed of excretion of TiO2 so that it has excreted half of the initial concentration (T1/2), and time to reach the balance of excretion of the marker (T (a+b)). There was no difference between treatments for the values of a, c, mean T and T, but there was a significant difference in the value of b between the administration of the marker of 2.5 vs 5 g (p<0.0001). The averages of faecal production estimated with TiO2 vs. faecal production observed directly was different in T1.25(2), T5(1) and T2.5(2) (p<0.05), but not in T2.5(1). In conclusion, the time in which the excretion equilibrium of TiO2 is reached is approximately eight days and the dose of 2.5 g of TiO2 once a day more accurately estimates faecal production in alpacas.